گرفتە كۆمەڵایەتی ودەروونییەكانی نەوجەوانان لە خانەكانی نەوجەوانان توێژینەوەیەكی مەیدانیە لەپارێزگای سلێمانی - عبدالله, كوێستان علی (Sulaimani Journal for Humanities, 2017)
Nonrandom sampling was the dependent methodology to select the population of the study, consequently, the percentage of male participation was (%55.5), whereas the percentage of female participation was (%44.4). As a result of conducting this study, many results were highlighted. First, the study concluded that deprived children represent the majority in Juvenile Detention Centers. Next, the study investigated the common psychological and social problems that face juveniles of both sex during their staying in the Juvenile Detention Center, as a result, the study found that they feel anxiety most of the time due to aggression, shame, fear and other problems related to the search for identity as well as poor communication with peers.Then, the study found that (%75) of the total population of the study are willing to leave the detention centers and return to the warmth of their families, for family is the fundamental institution to nurture individuals and to گۆڤاری زانکۆی سلێمانی/ بەشی )B )زانستە مرۆڤایەتییەکان ژمارە )58( تشرینی یەکەمی 8108 741 build the sense of attachment and happiness. The research also found that the communication between the juveniles and social workers and other members of detention centers is weak. A percentage of 55.5 of the juveniles complained that members of detention centers and social workers fail to perform their duties supposedly. Therefore, they tend to use violence to prevent disobeying. Consequently, the research displayed disappointments of the juveniles over the used programs and activities practiced by the detention centers which according to them do not answer their needs on one hand, and lacks variety on the other hand. Especially, for juvenile age they need opportunities to express themselves, grow skills and develop their cognitive, mental and physical abilities. The research found that juveniles experience fear, anxiety and strange feelings which in the event of continuation might result psychological disorder, it encourages juvenile to develop skills and fill the gaps caused be lack of love and compassion.This research, entitled “Psychological and Social Problems Confronting Juveniles in Detention Centers” is aiming to uncover psychological and social problems confronting juveniles in detention centers on one hand, and on the other hand to introduce this class to the society. Additionally, the study aims to display the programs and activities applied in the detention centers in order to approach fruitful programs and activities in the future to defy the challenges and to propose colorful programs and activities suitable for juveniles age. The current research consists of two main parts; theoretical and practical. The theoretical part is devoted to explain and analyze the topic theoretically. Therefore, it is divided into two chapters, the first chapter is divided to two sections. In the first section, the theoretical framework of the research is organized to includ problem and objectives of the research. While the second section is an introduction to terminology used in the research in order to make it easier on the reader. The composition of the second chapter is two sections as well. The first section deals with psychological and social problems that face juveniles in the detention centers. Whereas the second section displays the programs and activities presented in the detentions centers. The practical part is divided to two main chapters. The first chapter is appointed to introduce the methodology of the research. Thus, this chapter is divided to three sections. In the first section, we introduce the methodology and requirements of the practical part including methodology, data collecting tools, and statistical methods. The second section analyzes and discusses the charts. Finally, the third section is devoted for conclusions, recommendations and proposals.